Current Symptoms and Pathological Changes of Bursa Fabricius from Commercial Farming Broilers Led to Infectious Bursal Disease - Bernike Anggun Damairia; Khrisdiana Putri; Bambang Sutrisno; Michael Haryadi Wibowo (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
Infectious Bursal Disease (IBD) or Gumboro is caused by the IBD virus of the Birnaviridae family. The disease is acute and highly contagious in young birds. The virus infection causes severe damage to the lymphoid organs i.e. bursa Fabricius leading to immunosuppression. The disease morbidity may reach 100%, while the mortality varies from 20 to 100%, causing high economic losses. Infectious Bursal Disease has remained significant threat although vaccination has been applied. This study aimed to determine the current typical pathological changes in the bursa Fabricius of commercial broilers showing IBD symptoms. The samples were obtained from commercial broiler farms in Sragen, Wonogiri, Batang, and Sleman. Gross lesion examination showed enlargement of the bursa Fabricius with gelatinous material on the serosal surface, oedema with fluid accumulation in the lumen, hemorrhages of the serosal surface, atrophy, and caseous exudate in the lumen. Histopathologic changes of acute IBD include hemorrhages, congestion, lymphocyte necrosis, accumulation of fibrin, oedematous and heterophils infiltration in the interfollicular tissues. Microscopic changes in chronic IBD (5-7 days post infection IBDV) including follicular atrophy, lymphocyte necrosis, vacuolization of the follicle, and proliferation of fibroblast and connective tissue in the interfollicular space. In conclusion, the notable pathological change description of bursa Fabricius in suspected acute is gross lesion (swelling and edema, thickened and enlarged plica bursa Fabricius, hemorraghe), microscopic lesion (congestion, hemorraghe, heterophil infiltration) or chronically IBD infection in broiler chicken was gross lesion (atrophy bursa Fabricius, atrophy and excudate casouse in the lumen bursa Fabricius), microscopic lesion (lymphocyte necrosis, vacuolization of bursa Fabricius follicles, proliferation of fibroblasts and interfollicular connective tissue).